2019
DOI: 10.1111/jep.13255
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision‐making in mental and behavioural health interventions

Abstract: Elements of shared decision‐making (ie, collaboration, patient preferences, and working alliance) have long been discussed and studied in the field of clinical psychology; however, research indicates that shared decision‐making is not typically used in clinical practice. Instead, clinicians often rely on a paternalistic approach. In this article, we provide a narrative review of the existing research supporting shared decision‐making for mental and behavioural health concerns, we discuss several barriers that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
1
13
0
1
Order By: Relevance
“…Wenn für Patienten arbeitsbezogene Teilhabe zwar ein wichtiges Ziel darstellt, es in der klinischen Behandlung jedoch zu wenig thematisiert und konkret bearbeitet wird, kann dies zudem als unzureichender Konsens über Behandlungsziele zwischen Patienten und Therapeuten interpretiert werden. Diese fehlende Übereinstimmung wiederum kann sich nachteilig auf den Behandlungserfolg auswirken [27][28][29]. Eine Ursache für dieses Missverhältnis kann die Tatsache, dass Leistungen zur Verbesserung der Teilhabesituation im Rechtskreis des SGB V nicht explizit verankert sind [8,30,31], darstellen.…”
Section: Gruppenvergleiche Zwischen Patienten Mit Und Ohne Unterstützunclassified
“…Wenn für Patienten arbeitsbezogene Teilhabe zwar ein wichtiges Ziel darstellt, es in der klinischen Behandlung jedoch zu wenig thematisiert und konkret bearbeitet wird, kann dies zudem als unzureichender Konsens über Behandlungsziele zwischen Patienten und Therapeuten interpretiert werden. Diese fehlende Übereinstimmung wiederum kann sich nachteilig auf den Behandlungserfolg auswirken [27][28][29]. Eine Ursache für dieses Missverhältnis kann die Tatsache, dass Leistungen zur Verbesserung der Teilhabesituation im Rechtskreis des SGB V nicht explizit verankert sind [8,30,31], darstellen.…”
Section: Gruppenvergleiche Zwischen Patienten Mit Und Ohne Unterstützunclassified
“…Despite the increasing adoption of the recovery model (which focuses on empowering patients and growing their autonomy) and patients wanting to be part of SDM, many patients with serious mental illnesses are still not being involved in important decisions concerning their treatment [ 48 , 54 ]. Evidence suggests that active participation in treatment decisions leads to a greater likelihood of treatment initiation, reduced symptoms, improved self-esteem, increased service satisfaction, improved patient knowledge, increased confidence in decisions, more active patient involvement, decreased rates of hospitalization (in people with schizophrenia) and improved treatment adherence [ 48 , 52 ].…”
Section: Shared Decision-makingmentioning
confidence: 99%
“…Clinicians who are trained in a specific treatment, or who prefer a specific theoretical orientation can be inclined to advise a treatment according to their own preferences, which results in bias [ 23 ]. This process is enhanced by overconfidence in one's own judgement and a lack of regular monitoring of outcomes [ 52 ].…”
Section: Shared Decision-makingmentioning
confidence: 99%
“…Their starting point is the observation that little is known about the extent to which people with severe mental illness actually want to be involved in the decision‐making process. Their extensive study of outpatients with a range of mental disorders concluded that psychiatric patients “more frequently preferred a passive role in the decision‐making process” and that interventions to promote SDM need to be carefully tailored to the values and needs of each patient, “because not everyone wants to participate to the same degree.” While agreeing that “part of the SDM process entails allowing patients to not participate in SDM if that is their preference,” and that “pressuring patients to engage in SDM undermines the goals of this model,” Wilson Trusty et al also site research supporting SDM for mental and behavioural health concerns, providing recommendations for increasing SDM when working with patients. The need to be person‐centred, to tailor the approach to the specific needs and values of each patient, emerges from each article as an overriding concern if SDM is to be meaningful and actually helpful to clinicians and patients.…”
Section: Shared Decision Makingmentioning
confidence: 99%
“…It includes papers on the nature of reasoning and evidence, the on‐going problems of how to “integrate” different forms of scientific knowledge with each other, and with broader, humanistic understandings of reasoning and judgement, patient and community perspectives . Discussions of the epistemological contribution of patient perspectives to the nature of care, and the crucial and still under‐developed role of phenomenology in medical epistemology, are followed by a broad range of papers focussing on SDM, analysing its proper meaning, its role in policy, methods for realizing it and its limitations in real‐world contexts …”
Section: Introductionmentioning
confidence: 99%